Pro Bash Programming Scripting the GNU/Linux Shell - Johnson, Chris F. A.; SpringerLink (Online service) (Berkeley, CA : Apress, 2010)
The bash shell is a complete programming language, not merely a glue to combine external Linux commands. By taking full advantage of shell internals, shell programs can perform as snappily as utilities written in C or other compiled languages. And you will see how, without assuming Unix lore, you can write professional bash 4.0 programs through standard programming techniques. Complete bash coverage Teaches bash as a programming language Helps you master bash 4.0 features
Hello, World! Your First Shell Program -- Input, Output, and Throughput -- Looping and Branching -- Command-Line Parsing and Expansion -- Parameters and Variables -- Shell Functions -- String Manipulation -- File Operations and Commands -- Reserved Words and Builtin Commands -- Writing Bug-Free Scripts and Debugging the Rest -- Programming for the Command Line -- Runtime Configuration -- Data Processing -- Scripting the Screen -- Entry-Level Programming.
Keywords: Computer science; Computer Science; Programming Techniques